Effect of Stabilized Martensite on the Long-Term Performance of Superelastic NiTi Endodontic Files - Sánchez, Patricia; Vidi, Benedetta; Mena Álvarez, Jesús; Gil, Javier; Rico Romano, Cristina; Aragoneses, Juan Manuel (My University, 2023)
One of the most used rotary files in endodontics is NiTi files due to their superelastic properties. This property means that this instrument has extraordinary flexion that can adapt to large angles inside the tooth canals. However, these files lose their superelasticity and fracture during use. The aim of this work is to determine the cause of fracture of the endodontic rotary files. For this purpose, 30 NiTi F6 SkyTaper® files (Komet, Germany) were used. Their chemical composition was determined by X-ray microanalysis, and their microstructure was determined by optical microscopy. Successive drillings were carried out with artificial tooth molds at 30, 45, and 70¿ . These tests were carried out at a temperature of 37 ¿C with a constant load controlled by a high sensitivity dynamometer of 5.5 N, and every five cycles were lubricated with an aqueous solution of sodium hypochlorite. The cycles to fracture were determined, and the surfaces were observed by scanning electron microscopy. Transformation (austenite to martensite) and retransformation (martensite to austenite) temperatures and enthalpies were determined by Differential Scanning Calorimeter at different endodontic cycles. The results showed an original austenitic phase with a Ms temperature of 15 ¿C and Af of 7 ¿C. Both temperatures increase with endodontic cycling, indicating that martensite forms at higher temperatures, and the temperature must be increased with cycling to retransform it to austenite. This fact indicates the stabilization of martensite with cycling, which is confirmed by the decrease in both transformation and retransformation enthalpies. The martensite is stabilized in the structure due to defects and does not retransform. This stabilized martensite has no superelasticity and, therefore, fractures prematurely. It has been possible to observe the stabilized martensite by studying the fractography, observing that the mechanism is by fatigue. The results showed that the files fracture earlier the greater the angle applied (for the tests at 70¿ at 280 s, at 45¿ at 385 s, and at 30¿ at 1200 s). As the angle increases, there is an increase in mechanical stress, and, therefore, the martensite stabilizes at lower cycles. To destabilize the martensite, a heat treatment can be carried out at 500 ¿C for 20 min, and the files recovers all its superelasticity. Keywords: stabilized martensite; fatigue; superelasticity; NiTi; endodontics file